Ubiquitous but invisible – public librarians’ self-imposed professional information practices as articulation work - Ola Pilerot; Jenny Lindberg (Information Research: An International Electronic Journal)
Introduction. To do a good job, public librarians must stay informed and updated on matters related to their work. Seeking and making use of information is ubiquitous in librarians’ everyday work life but this part of their work is elusive and hard to identify. This paper presents a study of how Swedish public librarians keep updated with professional information. It aims to elucidate the parts of this work that occur silently and often outside of formal working hours.